Hollanda Loyola, educação e educação física : reflexões pedagógicas e prescrições educacionais (1934-1944) - Freitas, Luana Luzia Lóss de (2011)
This study investigates the representations and recommendations devised by Hollanda Loyola about a Pedagogy focused on Physical Education and Physical Education for Children. The study uses three kinds of printed media as source of information (newspaper, journal and books), which are the avenues used by this social actor to convey his productions. The publications examined were the integralist newspaper A Offensiva, published between the years of 1934 and 1938; the journal Educação Physica, published for the first time in 1938 and ended in 1945; and his 12 books published by Cia. Brasil Publisher. The analysis was based on the propositions of Cultural History, opting for an investigation based on micro-history, not only to describe, but also to interpret the events and then, to understand the social reality (macro) through the analysis of practices (individual or in a group) of ownership and representation. In order to delineate the links among the struggles of representation, the study focuses on concepts of strategy and tatics of Michel De Certeau. It tries to understand Hollanda Loyola as an actor/author/editor that sits strategically/tactically according to the game that is being played in politics and culture in the 1930s and 1940s, to define the path that Brazil would follow after the Revolution of 1930. Investigating his recommendations about Pedagogy and Physical Education, the study finds that these propositions are practices of appropriation and transformation of knowledge that, back in the 1930s and 1940s, represented one of the most modern in terms of pedagogical reflection. With a good knowledge in Physiology, Biology, and Psychology, he decides to (re)think in detail a method of Physical Education that can be used for all ages (from birth to the end of the life), suitable to the Brazilian reality. Reflecting about a “Physical Education P lan” for all ages, Loyola also organizes a proposal for Physical Education that looks at the specificities of Child Education. According to him, the childhood was a prominent stage in the life of a man, filled with intrinsic characteristics that needed to be respected, mainly because, at this stage it would be easier to shape/correct the character and prevent the children from being corrupted, a fact that would make more difficult the training of the “new man”, patriotic and industrious, necessary to the modern society that was sought to be built in the 1930s and 1940s.